A Capela de Nossa Senhora do Rosário dos Pretos em Pirenópolis – história e memória (1743-1944). - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The central problem of this dissertation is the analysis of the historicity of the construction of a “black” Catholic chapel - the Igreja do Rosário dos Pretos de Pirenópolis - in 1743, in Pirenópolis, Goiás, from the period of its structural existence, which led to the symbolic construction of the landmarks of remembrance and oblivion with its demolition in 1944. The hypothesis seeks to elucidate whether the construction of a public cemetery in the city was a decisive factor in why it was no longer necessary to perform funeral rituals inside the chapel and on its banks. Methodologically, the approach is historiographical, based on a documentary survey of the cultural history of socially marginalized black people. In this way, the research proposes a bibliographical review of studies on the subject, as well as archives in the parish office, where the book of the members who built the chapel and other people who took part in the congregation of the same name is kept. In this context, the basic theoretical framework is based on Michel de Certeau (The Writing of History), Clifford Geertz (The Interpretation of Cultures) and Walter Benjamin, more broadly. In the local Brazilian context, Maria Lemke Loiola, Nasr Chaul and Cristina de Cássia Moraes are cited as theoretical references. The problematization is also based on an analysis of the social functioning of the chapel, a sacred place of refuge for its practitioners, its administration, the benefits for attendees of the religious temple and the obligations offered specifically to the saints of the Brotherhoods, who had their representations installed on the altars of the church. The dissertation is divided into an introduction, three chapters and final considerations. The first chapter is entitled ‘From the pages of notebooks to the walls’ and has two subdivisions: ‘The dawn of the chapel of Nossa Senhora do Rosário dos Pretos in Meia Ponte’ and ‘Particularities, members’ books and symbologies of the church’. The second chapter is entitled ‘Bonds of belonging of the sectarians of the Chapel’ and is made up of two subdivisions: ‘The groups that attended the church and their bonds’ and ‘Singularities, benefits and distinctions of the Chapel of Na. Sa. do Rosário dos Pretos’. The third chapter is entitled ‘Nothing will remain standing’ and three other subheadings: ‘The impact of abolition on slavery’, ‘Forms of undermining the symbolic spaces of black people in Meia Ponte’ and ‘House of God, house of the dead’.
The Chapel of Our Lady of the Rosary of Blacks in Pirenópolis – history and memory (1743-1944)
Keywords: Capela de Nossa Senhora do Rosário dos Pretos - Escravidão - Pirenópolis; Escravidão - Pirenópolis - Esquecimento; Chapel of Our Lady of the Rosary of the Blacks - slavery - Pirenópolis; Slavery - Pirenópolis - Oblivion; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::HISTORIA; GEOGRAFIA::GEOGRAFIA HUMANA